Ensino do Direito do Trabalho no Brasil: desvela a realidade ou reproduz a lógica do capital? - Barros, Renato Cassio Soares de (Universidade Federal de São Carlos, 2015)
This thesis aims at analyzing the education of bachelor of laws regarding the teaching of Labor Law in Brazil to investigates if this study emancipates or has the purpose of maintaining the capital, instrumentalized by the empire of fragmented and legalistic education. For this, a discussion of the Labor Law in capitalism was done, with regulation of labor by Law and its historical process, through the thought of Karl Marx on the legal socialism, the formation of the working class and the antagonism of classes, as well as about state intervention in labor relations in Brazil. Then, the research focused on the analysis of Labor Law books adopted by some colleges in Brazil, evaluating whether they have the Labor Law in a critical dimension, drawing upon historical, political, philosophical, economic and sociological aspects. Reflect on the possibility of social emancipation through the Labor Law and what is its function in teaching at Law Schools was a significant challenge, allowing the questioning about the authority of the law doctrine and the fragmentation of education which does not reach the essence, since it does not dialogue with other knowledge areas and, at best, is just a non-organic dialogue throughout the text. Based on the analysis, it was found that the Labor Law has as main objective the order maintenance. Thus is necessary to question the possibility of using Labor Law to better social conditions of the working class until a possible emancipation in a perspective in which the law school graduate, the jurist and who deals with law in general, cannot ignore this understanding, regardless of position on the production relations.
Keywords: Direito Estudo e ensino; Direito do trabalho; Lógica do capital; Teaching of labor law; Labor law; The logic of capital; CIENCIAS HUMANAS::EDUCACAO